Interpretations of aftershock advice and probabilities after the 2013 Cook Strait earthquakes, Aotearoa New Zealand. (October 2020) - Doyle, Emma E.H.; McClure, John; Potter, Sally H.; Lindell, Michael K.; Becker, Julia S.; Fraser, Stuart A.; Johnston, David M.
Abstract: Probabilistic statements can be a valuable tool for natural hazard risk communication, including forecasts. However, individuals often have a poor understanding of such probabilistic forecasts caused by them distorting their interpretations of event likelihoods towards the end of the time window and discounting the risk today. We investigated the use of an 'anchoring' time statement to mitigate this bias via an opportunistic survey run after the 2013 Cook Strait earthquakes, near Wellington, New Zealand. Participants rated their interpretations of likelihoods for an immediate aftershock forecast, and for an earthquake in the future. We explored the influence of aftershock and information concern, emotions and felt shaking, gender and education, as well as preparedness actions. The anchoring time window statement mitigated the skew in interpretations for the short (24 h to within 1 week) aftershock forecast statement. However, the skew still existed for the longer future earthquake forecast (7 days to within 1 year). We also found that heightened sensory experience (felt shaking) or emotional reactions (nervousness, fear, alertness) during the earthquakes was associated with an increase in the perceived likelihoods of future events. Gender was found to significantly influence results, with females rating higher levels of information concern and anxiety, and recording higher perceived likelihoods for the immediate aftershock forecast. Findings, including the importance of 'anchoring' time windows within a forecast to encourage immediate preparedness actions, support recommendations for effective crafting of these forecasts and warnings. Highlights: We investigate interpretations of likelihood based on earthquake and aftershock forecasts. An anchoring window mitigates a discounting of likelihood through time; recommendations are given for forecast messaging. This anchoring mitigation is seen for short, but not long, time windows. Females recorded higher information concern and anxiety, and higher perceived likelihoods. A heightened sensory, or emotional, experience in an earthquake was associated with an increase in perceived likelihoods.